Lack of Rule-Adherence During Mountain Gorilla Tourism Encounters in Bwindi Impenetrable National Park, Uganda, Places Gorillas at Risk From Human Disease - Weber, Annalisa; Kalema-Zikusoka, Gladys; Stevens, Nancy J. (Frontiers in Public Health, 2020)
Mountain gorillas (Gorilla beringei beringei) are an endangered primate species, with approximately 40% of the 1000 individuals that remain on the planet today residing in Bwindi Impenetrable National Park (BINP) in southwestern Uganda. These primates are at the heart of a growing tourism industry that has incentivized their continued protection, but close proximity between humans and gorillas during such encounters presents well-documented risks for disease transmission. The Uganda Wildlife Authority (UWA) has developed rules to help protect the health of the gorillas, limiting each habituated gorilla group to a single 60 minute visit each day by a group of no more than 8 tourists, and emphasizing that humans maintain a >7 m distance from gorillas at all times. A number of studies have documented that not all tour groups respect these rules. This project assesses rule-adherence during gorilla tourism encounters at BINP using both observational and survey-based data collected during the tourism high season between May-August, 2014. Observational data from 53 treks reveal that groups of 2-10 tourists engaged in gorilla viewing encounters between 46-98 minutes in duration. Although 96% of pre-trek briefings conducted by park wardens emphasized the need to maintain > 7 m human-gorilla spacing, the 7 m distance rule was violated in over 98% (52 out of 53) of tours examined in this study. During the encounters, observational data were collected at two minute intervals, documenting the nearest distance between any tourist and a gorilla (n=1604), of which 1094 observations (68.2%) took place at a distance less than or equal to 7 m. Importantly, the 7 m rule was violated in visits to all of the gorilla groups habituated at the time of the study. In 224 observations, human-gorilla spacing was 3 m or less. Survey data (n=243) revealed promising opportunities to improve tourist understanding of and adherence to park rules, with 73.6% of respondents indicating that they would be willing to utilize a precautionary measure of wearing a facemask during encounters to protect gorilla health.